Poros Maritim Dunia Sebagai Pendekatan Strategi Maritim Indonesia: Antara Perubahan Atau Kesinambungan Strategi? - Probo Darono Yakti; Joko Susanto (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2017)
As a nation-state located in a cross-position, Indonesia proposes a maritime strategy approach in the form of the Global Maritime Fulcrum (GMF). To some extent, GMF introduces an advanced concept from the previous maritime strategy. Therefore this explanative research will explore further about concepts related to change or continuity, related to the maritime strategy of Indonesia in the previous periods before GMF. Based on field data, this research found a number of facts that concludes GMF to some extent is a change from previous maritime strategy. Moreover, the debate of Indonesia’s geographical position could be interpreted as a response against threats which already exists. Thus this condition experienced a shift due to the dynamics of international politics. This qualitative research also conducts that GMF is a value which inherited from previous administration to further adapt on contemporary situations. Thus in general these findings indicate that GMF is a change from the previous maritime strategy.